Laparotomy in women with severe acute maternal morbidity: secondary analysis of a nationwide cohort study - Tom Witteveen; Athanasios Kallianidis; Joost J. Zwart; Kitty W. Bloemenkamp; Jos van Roosmalen; Thomas van den Akker (BMC, 2018)
Abstract Background Although pregnancy-related laparotomy is a major intervention, literature is limited to small case-control or single center studies. We aimed to identify national incidence rates for postpartum laparotomy related to severe acute maternal morbidity (SAMM) in a high-income country and test the hypothesis that risk of postpartum laparotomy differs by mode of birth. Methods In a population-based cohort study in all 98 hospitals with a maternity unit in the Netherlands, pregnant women with SAMM according to specified disease and management criteria were included from 01/08/2004 to 01/08/2006. We calculated the incidence of postpartum laparotomy after vaginal and cesarean births. Laparotomies were analyzed in relation to mode of birth using all births in the country as reference. Relative risks (RR) were calculated for laparotomy following emergency and planned cesarean section compared to vaginal birth, excluding laparotomies following births before 24 weeks' gestation and hysterectomies performed during cesarean section. Results The incidence of postpartum laparotomy in women with SAMM in the Netherlands was 6.0 per 10,000 births. Incidence was 30.1 and 1.8 per 10,000 following cesarean and vaginal birth respectively. Compared to vaginal birth, RR of laparotomy after cesarean birth was 16.7 (95% confidence interval [95% CI] 12.2-22.6). RR was 21.8 (95% CI 15.8-30.2) for emergency and 10.5 (95% CI 7.1-15.6) for planned cesarean section. Conclusions Risk of laparotomy, although small, was considerably elevated in women who gave birth by cesarean section. This should be considered in counseling and clinical decision making.